The Demersal Fishing Capability Landed at Kema Dua Fish Landing Base North Minahasa: Kemampuan Tangkap Perikanan Demersal Yang Didaratkan Di Pangkalan Pendaratan Ikan Kema Dua Minahasa Utara - Mervin Lestaluhu; Alfret Luasunaung; Mariana Kayadoe; Revols D.Ch. Pamikiran; Ivor L. Labaro; Fanny Silooy (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2023)
This study aims to determine the catch and development of CPUE from catches landed at the Kema Dua Fish Landing Base. The method used in this study is the Descriptive Method. The data collected is in the form of primary data by observation and interviews and secondary data in the form of catches and fishing efforts from 2017-2021. The data obtained will be analyzed using graphs and CPUE calculations to determine the development between production (catch) and capture effort (effort). Based on the results of the research carried out, it can be concluded that the bottom fishing catch landed at the Kema Dua Fish Landing Base consists of 9 types of demersal fish, namely Saramia fish (Etelis Carbunculus) 526,990 kg (25.5%), Lolosi (Caesio cuning) 459,855 kg (22.2%), Tola (Pristipomoides filamentosus) 404,490 kg (19.5%), Tariasan (Aphareus rutilans) 323,910 kg (15.6%), and Kurisi (Nemipterus sp) 213,675 kg (10.3%), Rahiang (Etelis coruscans) 53,300 kg (2.6 %), Kuwe (Carangoides coeruleopinnatus) 42,285 kg (2.0 %), Snapper (Lutjanus sp) 27,100 kg (1.3 %), Grouper (Epinephelus sp) 18,390 kg (1.0 %). The development of the Catch value per Unit Effort (CPUE) for 5 years (2017-2021) based on the catch landed at PPI Kema Dua fluctuates every year. The highest CPUE value occurred in 2021 at 3,452 kg/trip and the lowest CPUE value occurred in 2019 at 2,670 kg/trip.